2007
DOI: 10.3748/wjg.v13.i3.426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of COX-2, PCNA, Ki-67 and p53 in gastrointestinal stromal tumors and its relationship with histopathological parameters

Abstract: AIM:To investigate the expression of Cyclooxygenase-2 (COX-2), proliferating cell nuclear antigen (PCNA), Ki-67 and p53 in gastrointestinal stromal tumors (GISTs) and its relationship with histopathological parameters. METHODS:Twenty-five GISTs were examined by light microscopy and immunohistochemistry. c-kit, CD34, SMA, S-100 protein, COX-2, PCNA, Ki-67 and p53 were detected immunohistochemically and the relationship was evaluated among histopathologic parameters such as mitotic index (MI), tumor grade, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
14
2
Order By: Relevance
“…However, the majority of these studies, as well as ours, were limited by the fact that most of the statistically significant variables based on univariate statistics are not statistically strong enough to 'surviveʼ a further multivariate analysis, leading to the heretic question of whether IHC does actually provide additional prognostic data in GISTs (18). Furthermore, we were unable to confirm the role of differentiation and cell-cycle regulatory proteins, such as Bcl-2, P16 and P53, as well as CD44, as prognostic factors, similar to previous studies (8,(21)(22)(23)(24). The reasons may be different antibodies, antigen retrieval or inter-observer variations of the immunohistochemical staining (10,11,15).…”
Section: Discussioncontrasting
confidence: 41%
“…However, the majority of these studies, as well as ours, were limited by the fact that most of the statistically significant variables based on univariate statistics are not statistically strong enough to 'surviveʼ a further multivariate analysis, leading to the heretic question of whether IHC does actually provide additional prognostic data in GISTs (18). Furthermore, we were unable to confirm the role of differentiation and cell-cycle regulatory proteins, such as Bcl-2, P16 and P53, as well as CD44, as prognostic factors, similar to previous studies (8,(21)(22)(23)(24). The reasons may be different antibodies, antigen retrieval or inter-observer variations of the immunohistochemical staining (10,11,15).…”
Section: Discussioncontrasting
confidence: 41%
“…Liu et al (2005) demonstrated that PCNA index was correlated with necrosis, high grade atypia, cellularity and mitotic rate. In contrast, Gumurdulu et al (2007) did not Wnd a correlation of PCNA expression with survival in GISTs. Our observation showed that PCNA expression was lower in imatinib-responsive GISTs than acquired resistance tumors, suggesting that PCNA may act as the marker of GIST imatinib response.…”
Section: Discussionmentioning
confidence: 57%
“…Ki-67 antigen is expressed in proliferative cells throughout the G1, S, G2, and M phases, and provides a reliable index of cellular proliferation 3,4 PCNA is an acidic nuclear protein, expressed mainly in phase S of the cellular cycle. It becomes active, in various tissues par-ticularly in nervous tissue, as a first response to multiple insults.…”
mentioning
confidence: 99%